Does Ralstonia eutropha, rich in poly‐β hydroxybutyrate (PHB), protect blue mussel larvae against pathogenic vibrios?. Issue 6 (8th March 2019) - Van Hung, Nguyen; Bossier, Peter; Hong, Nguyen Thi X.; Ludeseve, Christine; Garcia‐Gonzalez, Linsey; Nevejan, Nancy; De Schryver, Peter
Abstract: The natural amorphous polymer poly‐β‐hydroxybutyrate (PHB‐A: lyophilized Ralstonia eutropha containing 75% PHB) was used as a biological agent to control bacterial pathogens of blue mussel ( Mytilus edulis ) larvae. The larvae were supplied with PHB‐A at a concentration of 1 or 10 mg/L for 6 or 24 hr, followed by exposure to either the rifampicin‐resistant pathogen Vibrio splendidus or Vibrio coralliilyticus at a concentration of 10 5 CFU/ml. Larvae pretreated 6 hr with PHB‐A (1 mg/L) survived a Vibrio challenge better relative to 24 hr pretreatment. After 96 hr of pathogen exposure, the survival of PHB‐A‐treated mussel larvae was 1.41‐ and 1.76‐fold higher than the non‐treated larvae when challenged with V. splendidus and V. coralliilyticus, respectively. Growth inhibition of the two pathogens at four concentrations of the monomer β‐HB (1, 5, 25 and 125 mM) was tested in vitro in LB35 medium, buffered at two different pH values (pH 7 and pH 8). The highest concentration of 125 mM significantly inhibited the pathogen growth in comparison to the lower levels. The effect of β‐HB on the production of virulence factors in the tested pathogenic Vibrios revealed a variable pattern of responses.